Youth’s climate consciousness: unraveling the Dengue-climate connection in Bangladesh - Siddique, Abu Bakkar; Hasan, Maruf; Ahmed, Ayesha; Rahman, Md Hafizur; Sikder, Md Tajuddin (Frontiers in Public Health, 2024)
Background Climate change affects the transmission of vector-borne diseases like dengue, posing a substantial public health threat. Bangladesh, with its favorable conditions for Dengue transmission, has experienced periodic outbreaks. This study explores the relationship between climate change knowledge, perceptions of the Dengue-climate link, and the associated factors among Bangladeshi youth. Methods In the Dhaka district of Bangladesh, a cross-sectional study was conducted between September and October 2023, involving face-to-face interviews with 1,358 participants. Convenient (non-probability) sampling was utilized for participant selection. Data collection involved the administration of a semi-structured questionnaire encompassing informed consent, socio-demographic information, and inquiries pertaining to climate change-related knowledge (13 items) and perception (11 items). Data analysis utilized STATA (Version 15.0) and SPSS (Version 26.0). Results The mean scores for knowledge and perceptions were determined to be 7.10 ± 3.20 (out of 13) and 26.60 ± 4.12 (out of 33) respectively. Participants had a mean age of 22.02 ± 1.58 years. The study revealed that unmarried status, living in a nuclear family, being a non-smoker, good self-perception of physical health, regular sleep patterns, moderate social media usage, older age, unemployment, and daily media consumption are factors associated with higher knowledge and perception regarding the Dengue-climate change link. Moreover, a positive association was observed between knowledge of climate change and favorable attitudes toward the Dengue-climate connection. Conclusion This study underscores the importance of tailored climate change education for youth in Bangladesh and highlights key variables influencing their knowledge and perceptions. Notably, there exists a positive association between climate change knowledge and favorable attitudes toward the Dengue-climate connection. These insights underscore the importance of targeted educational campaigns and policy interventions aimed at enhancing climate consciousness among the youth population, thereby fostering proactive measures to mitigate the impact of Dengue fever in the context of climate change.